Pencegahan Lesi Aterosklerosis Oleh Asam Alfa Lipoat Pada Aorta Mencit Jantan (Mus Musculus) Yang Diberi Diet Tinggi Kolesterol - Ismawati Ismawati; Winarto Winarto; Rezki Permata Sari (Fakultas Kedokteran Universitas Riau, 2011)
Atherosclerosis can happen easily on animal that are given high cholesterol diet. Alpha lipoic acid is universal antioxidantthat very effective to reduce free radicals, include lipid peroxide. The goal of this research was to find out the prohibitionof atherosclerosis lesion development on male mice aorta that was given high cholesterol diet by alpha lipoic acid. Thiswas an experimental laboratory research with post test only design. Eighteen adult male mice were segregated intothree groups labelled as group NaCl 0,9%, yolks and ALA.. The experiment was design for 6 weeks. The measuredparameter was atherosclerosis lesion score of groups labelled. The statistical test result showed the significant differenceof some tested groups. There was a statistically significant difference between alpha lipoic acid and yolks group (p=0,008),but there is no significant difference was found between ALA and NaCl 0,9% group (p=0,126). As the conclusion, thisstudy proves that alpha lipoic acid has the effects to prohibition of atherosclerosis lesion development on male miceaorta that are given high cholesterol diet.